Roles of the Kingdom of Saudi Arabia Toward the Development of Knowledge and Ulama - Ganefri, Ganefri; Anwar, Fuady; Murniyetti, Murniyetti; Zein, Zainurni; Rahayu, Sutria (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2017)
The Kingdom of Saudi Arabia is one of the largest Islamic countries lies in Arabian Peninsula. The government bases its legitimacy on its interpretation of Sharia (Islamic law) and the 1992 Basic Law. The Basic Law sets out the system of governance, rights of citizens, and powers and duties of the government. The law also provides that the Qur'an and the Traditions (Sunna) of the Prophet Muhammad serve as the country's constitution.Â As an Islamic country which is rich in culture and natural resources, the Kingdom of Saudi Arabia plays prominent influence in Islamic world for various aspects in politics, culture, economics, trading and education. The contribution of the Kingdom of Saudi Arabia can be clearly seen in education sector, particularly in Al-Quran and Sunnah studies. The country provides a wide opportunity and great facilitation for those who wants to study in Saudi Arabia in their own country. The founding of the Institute of Islamic and Arabic Science (LIPIA) in Indonesia as an important affiliation of Al Imaam University is regarded as real concern of Saudi Arabia in Islamic studies development. Further, pursuant to history of the Kingdom of Saudi Arabia, ulama plays respected crucial roles in the government. They are not merely respected for the high and exclusive knowledge in religion, but they are also regarded having capability in balancing the stability of the country. It implies that the government and ulama mutually work to protect the glory of Islam and the Kingdom